Diplomasi Tingkat Tinggi: Sebuah Pemahaman Awal - Zulkarnain Zulkarnain (Populis : Jurnal Sosial dan Humaniora, 2018)
AbstractSummit diplomacy belongs to the head of state or head of government. It will happen when there are crucial problems faced by the countries concerned and directly touch the collective interests of two or more countries involved in the summit. Summit or high-level diplomacy is also a reflection of a quick response by the parties that tends to produce a weighted agenda, so high-level diplomacy is not a series of activities of heads of state or heads of government filled with imaging missions, but rather an important mission for the national interest. One of the most important things of high-level diplomacy is the "ideology" of high-level diplomacy itself, namely the preparation of strategies, coordination and implementation measures aimed at the achievement of targets and objectives. That way, summit diplomacy avoids the blowing winds that pass without meaningful impression to mankind. Key words : diplomacy, summit diplomacy, national interest